Laia Villegas y Óscar Pujol (2017). Diccionario del yoga. Historia, práctica, filosofía y mantras. Barcelona: Herder, 300 pp. - Muñoz, Adrián (Estudios de Asia y África, 2018)
Laia Villegas y Óscar Pujol (2017). Diccionario del yoga. Historia, práctica, filosofía y mantras. Barcelona: Herder, 300 pp.